2006
DOI: 10.1089/jpm.2006.9.912
|View full text |Cite
|
Sign up to set email alerts
|

Caring for a Loved One with Advanced Cancer: Determinants of Psychological Distress in Family Caregivers

Abstract: Family caregivers of patients in the advanced stages of cancer experience a high level of psychological distress, which increases significantly as the patient loses autonomy. Health care policies and programs need to be revisited in order to take the reality of these patients and their families into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
168
3
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(198 citation statements)
references
References 43 publications
17
168
3
10
Order By: Relevance
“…It is stated that the disease, side effects and complications resulting from the treatment, repeated hospitalization, treatment's lasting too long, and disease's causing metastasis causes patients' wellness to impair, their family/marriage/business life, health condition and social life to be affected negatively from this process; caregivers experience more emotional confusion, tension, anxiety, depression, fatigue, role conflict, social isolation and problems than the patients; different psychiatric problems and advanced level of anxiety problems such as stress disorder after trauma may appear on care givers and as a result of these, their immune systems is impaired and physical disease risks are generated (Carter, 2005;Gaugler et al, 2005;Grov et al, 2005;Dumont et al, 2006;Given et al, 2006;Kitrungrote and Cohen, 2006;Langer et al, 2007;Mystakidou et al, 2007;Simmons, 2007). In litterateur, it is stated that as the problems of the patients increase and as the symptoms become more uncontrollable, the burden, depression, tendency of anxiety and sleep disorders of family members increase and their life quality reduces (Carter, 2005;Grov et al, 2005;Dumont et al, 2006;Mystakidou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is stated that the disease, side effects and complications resulting from the treatment, repeated hospitalization, treatment's lasting too long, and disease's causing metastasis causes patients' wellness to impair, their family/marriage/business life, health condition and social life to be affected negatively from this process; caregivers experience more emotional confusion, tension, anxiety, depression, fatigue, role conflict, social isolation and problems than the patients; different psychiatric problems and advanced level of anxiety problems such as stress disorder after trauma may appear on care givers and as a result of these, their immune systems is impaired and physical disease risks are generated (Carter, 2005;Gaugler et al, 2005;Grov et al, 2005;Dumont et al, 2006;Given et al, 2006;Kitrungrote and Cohen, 2006;Langer et al, 2007;Mystakidou et al, 2007;Simmons, 2007). In litterateur, it is stated that as the problems of the patients increase and as the symptoms become more uncontrollable, the burden, depression, tendency of anxiety and sleep disorders of family members increase and their life quality reduces (Carter, 2005;Grov et al, 2005;Dumont et al, 2006;Mystakidou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In litterateur, it is stated that as the problems of the patients increase and as the symptoms become more uncontrollable, the burden, depression, tendency of anxiety and sleep disorders of family members increase and their life quality reduces (Carter, 2005;Grov et al, 2005;Dumont et al, 2006;Mystakidou et al, 2007). Mothers participate more in care of child during the disease and working mothers have to quit their jobs.…”
Section: Introductionmentioning
confidence: 99%
“…Findings support the position that caring for a family member with cancer is a stressful life event (Dumont et al, 2006). Dealing with occurrences in everyday life coupled with the strains associated with the caregiving role and dealing with the healthcare system are contributing factors that can make grief and the bereavement experience difficult for FCGs of cancer patients.…”
Section: Discussionmentioning
confidence: 52%
“…17e19 Implicit in findings from these studies is that not every caregiver found the role positive, with some evidence of caregiver distress increasing over time. 37 Do These Findings Differ From Any Other Reported Data? The fact that spousal caregiver status does not help to predict a future unwillingness to care is of note, given the health and mortality effects on spouses who have provided care at the end of life without the support of specialist palliative care services.…”
Section: Discussionmentioning
confidence: 73%
“…Views are maintained over five years since caring at a constant rate. The most surprising aspect of these findings is the factors that are not predictive of future unwillingness to caredbeing the spouse of the deceased (given some of the other associations that have been noted in the literature 24 ), the person's diagnosis, 9,24,35e37 perceived levels of unmet needs (despite evidence that caregivers with depression have increased levels of unmet needs 37 and there are specific tasks they would prefer not to undertake 8 ), and the use of specialist palliative care services. 30 …”
Section: Key Resultsmentioning
confidence: 94%